MANAJEMEN PARIWISATA OLEH DINAS KEPEMUDAAN, OLAHRAGA DAN PARIWISATA KABUPATEN PEKALONGAN (Studi Pada Objek Wisata Kepemilikan Pemerintah Kabupaten Pekalongan - Alif Fajar Sidiq; Ida Hayu Dwimawanti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
Pekalongan Regency has a complete tourism potential, starting from the potential of nature tourism, cultural tourism, shopping tourism, and religious tourism, which can provide benefits to the region and the community if managed properly. However, in reality, tourism in Pekalongan Regency has not been able to compete, tourist arrivals are low so that in 2018 Pekalongan Regency placed 24th out of 35 regencies / cities in Central Java based on the number of tourist visits. This study aims to explain how tourism management is carried out by the Department of Youth, Sports and Tourism of Pekalongan Regency and its inhibiting and driving factors. Research analysis based on Tourism Destination Management theory includes planning, organizing, implementing programs, and monitoring. This research uses qualitative methods by collecting data through interviews, observation, documentation, and literature study. The results showed that tourism management was not optimal because there were various problems, namely lack of understanding of the organization's vision, limited budget, lack of numbers and competence of human resources, lack of attractions and attractions, tourism promotion was not optimal and supervision was not comprehensive. Driving factor is the large tourism potential and the support of the central and provincial governments. Other inhibiting factors are lack of community role, rob, unsterile tourism object from community activities, illegal parking, and lack of investors. Researchers recommend collaboration with third parties, add attractions and tourist attraction facilities, explore new tourism potential, follow tourism trends, create digital TIC, improve employee competency, recruit social media admins, create promotion innovations, comprehensive supervision, regulate illegal parking, and collect data and arrangement of traders in tourist attractions.